Inonotus rickii (Pat.) Reid: an important legnicolous basidiomycete in urban trees - Ramos,Ana Paula (2008)
Inonotus rickii is a basidiomycete that causes cankers and decay in several ornamental trees, and has been reported in Portugal since 2002. The aim of the present work was to evaluate the incidence of the disease caused by I. rickii on Celtis australis, in the community of Alcântara, Lisbon, where the European hackberry tree is the main sidewalk species. Disease incidence reached 19%, and affected trees showed sparse foliage, death of branches and white rot of heartwood. In some cases, chlamydospores masses and basidiocarps occurred on trunks and branches, especially on trees with more than 40 cm of DBH. Considering the increasingly importance of I. rickii and being C. australis one of the most important ornamental species used in the green areas of Lisbon, morphological and cultural characteristics of the pathogen are presented and its impact as agent of decline of urban trees is discussed.